Work Motivational Factors Affecting Job Performance among government Servant - Noor, Noor Farhana; Ali, Syukrina Alini Mat; Yunus, Noor’ain; Jailani, Sri Fatiany Abdul Kader (Advances in Social Sciences Research Journal, 2023)
Given the increasing job performance among employees, the purpose of this study is to investigate the motivating factor that leads to job performance among employees in the public sector at Putrajaya. The questionnaire was distributed to 200 employees at the headquarters of Jabatan Kehakiman Syariah Malaysia (JKSM) using convenience sampling. Analysis was conducted using SPSS Statistic 26 to investigate the relationship between motivation variables that can influence employee job performance. The results revealed that workplace design and job performance have a significant correlation while the reward element does not show a significant relationship with job performance. As a result, Malaysian public institutions in Malaysia can use the data acquired and the conclusion drawn to improve work performance among their employees. In addition, this study can enrich the existing literature and provide additional information for future research. Aside from that, this research can directly assist an organization in designing a better plan for establishing a better program or activities for their employees.